2003
DOI: 10.1242/jcs.00384
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3: tricks of the trade for a multi-tasking kinase

Abstract: Glycogen synthase kinase 3 (GSK-3) is a multifunctional serine/threonine kinase found in all eukaryotes. The enzyme is a key regulator of numerous signalling pathways, including cellular responses to Wnt, receptor tyrosine kinases and G-protein-coupled receptors and is involved in a wide range of cellular processes, ranging from glycogen metabolism to cell cycle regulation and proliferation. GSK-3 is unusual in that it is normally active in cells and is primarily regulated through inhibition of its activity. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
1,883
3
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,898 publications
(1,951 citation statements)
references
References 161 publications
38
1,883
3
11
Order By: Relevance
“…GSK3β activity is negatively regulated by phosphorylation on Ser9 by Akt, PKA, and PKC (Blomgren et al, 2007). Although the exact role of GSK3β in malignancies is still controversial due to conflicting results from different tumor models (Miyashita et al, 2009), inactivation of GSK3β is thought to contribute to the inhibition of tumor growth via cell cycle and apoptosis regulation (Doble and Woodgett, 2003;Luo, 2009). In this study, caffeine increased GSK3β phosphorylation at Ser9; this regulation was controlled by PKA.…”
Section: Discussionmentioning
confidence: 65%
“…GSK3β activity is negatively regulated by phosphorylation on Ser9 by Akt, PKA, and PKC (Blomgren et al, 2007). Although the exact role of GSK3β in malignancies is still controversial due to conflicting results from different tumor models (Miyashita et al, 2009), inactivation of GSK3β is thought to contribute to the inhibition of tumor growth via cell cycle and apoptosis regulation (Doble and Woodgett, 2003;Luo, 2009). In this study, caffeine increased GSK3β phosphorylation at Ser9; this regulation was controlled by PKA.…”
Section: Discussionmentioning
confidence: 65%
“…GSK-3b, a key player of the Wnt/b-catenin pathway is inhibited by phosphorylation at Ser9 [33]. This in turn prevents b-catenin from degradation and results in increased Wnt/b-catenin signaling [34]. Our immunocytochemistry showed that GSK-3[gr beta] is phosphorylated at Ser9 specifically at the apical surface (Fig.…”
Section: Polarity Protein Expression and Localization In Neural Diffementioning
confidence: 81%
“…2). LeishH1 was chosen because it 420 possesses the consensus recognition motif for phosphorylation by GSK-3β: S/TXXXS/T(P), where 421 X is any amino-acid (Doble and Woodgett, 2003). LdGSK-3s shows no autophosphorylation when 422 the kinase assay is performed without substrate (Fig.…”
Section: Ldgsk-3 S and Crk3 Inhibitor Screen 389mentioning
confidence: 99%